Evaluating the Economic Viability of Public Investments in Tourism - Banerjee, Onil (2018)
Various methods have been applied to evaluating the economic viability of public investments in tourism. In this paper, we capitalize on the strengths of general equilibrium and cost benefit analytical techniques and develop an integrated approach to evaluating public investments in tourism. We apply the approach to the evaluation of a US$6.25 million investment in tourism in Uruguay from the perspective of a multi-lateral development bank and a beneficiary government. The approach is powerful in that it captures first and subsequent rounds of investment impacts both on the benefits and costs side; resource diversion and constraints are accounted for, and; the estimation of benefits is consistent with the welfare economics underpinnings of cost benefit analysis.